Fairness and Cheating - Daniel Houser; Stefan Vetter; Joachim Winter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
We present evidence from a laboratory experiment showing that individuals who believe they were treated unfairly in an interaction with another person are more likely to cheat in a subsequent unrelated game. Specifically, subjects first participated in a dictator game. They then flipped a coin in private and reported the outcome. Subjects could increase their total payoff by cheating, i.e., lying about the outcome of the coin toss. We found that subjects were more likely to cheat in reporting the outcome of the coin flip when: 1) they received either nothing or a very small transfer from the dictator; and 2) they claimed to have been treated unfairly. This is consistent with the view that experiencing a norm violation is sufficient to justify the violation of another norm at the expense of a third party. This result extends the growing literature on social norms.
urn:nbn:de:bvb:19-epub-13219-0
Keywords: C91; D03; D63; 330; cheating; social norms; experimental design; Soziale Norm; Betrug; Spieltheorie; Test